"Brexit": A Case Study in the Relationship Between Political and Financial Market Uncertainty. (9th September 2016) - Smales, Lee A.
Abstract: This letter explores a single research question: How does political uncertainty, outside of the election cycle, influence financial market uncertainty? Using the UK (Brexit) referendum on EU membership as a novel event to examine this question, I identify a positive and well defined relationship between political and financial market uncertainty. Implied volatility in both UK and German financial markets rises as uncertainty around the polling result increases. Political uncertainty is most important for investors as the polling date draws near and in the instances when opinion polls indicate the outcome is particularly close. This result has implications for firms making financing and investment decisions, and investors making portfolio choices, around the time of important political events.